No correlation between wellness and countermovement jump in female collegiate lacrosse. Original Scientific Research Study - Frick, M. D.; Hamlet, M. D.; Tudini, F.; Bunn, J. A. (Journal of Australian Strength and Conditioning, 2021)
Self-reported wellness scores subjectively measure general fatigue from stressors and training load. Counter movement jump (CMJ) objectively measures neuromuscular fatigue. This study aimed to examine the correlation between self-reported wellness scores and CMJ in women`s collegiate lacrosse players and evaluate differences in wellness and CMJ during pre-season and in-season training. Athletes (n = 27) completed daily wellness surveys inquiring about muscle soreness, energy level, sleep, and stress, providing a composite wellness score (arbitrary units, AU). Athletes performed three maximal CMJ efforts at the start of each week. The average height of the three jumps was correlated with corresponding wellness scores. Trivial correlations between CMJ and wellness were found for the entire training year (r=.036, p=.808) and pre-season (r=.069, p=.257), and a low correlation was shown for in-season (r=.162, p=.837). There were differences between pre-season and in-season for wellness (pre-season: 70.2±19.1 AU, in-season: 74.7±15.7 AU, p=.017) and CMJ (pre-season: 48.0±4.8 cm, in-season: 46.9±4.8 cm, p=.030). There was no correlation found between CMJ and wellness scores either in season or pre-season. Thus, both objective and subjective assessments may be beneficial to assess athlete fatigue in a collegiate female population.